1965
DOI: 10.1104/pp.40.5.840
|View full text |Cite
|
Sign up to set email alerts
|

A survey of herbicides for their effect upon protein synthesis.

Abstract: The means by which many herbicides kill susceptible plants are presently unknown (1, 3). Although it is not essential to know the mode of action in order to develop and use a herbicide efficiently, the screening processes by which herbicides are discovered are based upon comparative biochemistry. Se

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
2

Year Published

1968
1968
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 1 publication
2
49
0
2
Order By: Relevance
“…Although microtubules, or microtubule associated material, are implicated as the target of IPC action in all of these studies, the wide variation in concentration of IPC used, the different assay methods, and the variable responses in these widely diverse organisms make it difficult to propose a uniform mode of action for IPC . In addition, earlier reports that the 3-chlorophenyl derivative of IPC, CIPC, inhibits protein synthesis in several plant systems (Mann et al ., 1965 ;1967) and the hypothesis that IPC and CIPC may inhibit messenger RNA transcription and hence, new protein synthesis (Mann et al ., 1967 ;Keitt, 1967) suggested that some of the responses listed above (e .g ., inhibition of cilia regeneration and flagellum morphogenesis) may be due to inhibition of protein synthesis, including the synthesis of microtubule protein .…”
Section: Discussionmentioning
confidence: 98%
“…Although microtubules, or microtubule associated material, are implicated as the target of IPC action in all of these studies, the wide variation in concentration of IPC used, the different assay methods, and the variable responses in these widely diverse organisms make it difficult to propose a uniform mode of action for IPC . In addition, earlier reports that the 3-chlorophenyl derivative of IPC, CIPC, inhibits protein synthesis in several plant systems (Mann et al ., 1965 ;1967) and the hypothesis that IPC and CIPC may inhibit messenger RNA transcription and hence, new protein synthesis (Mann et al ., 1967 ;Keitt, 1967) suggested that some of the responses listed above (e .g ., inhibition of cilia regeneration and flagellum morphogenesis) may be due to inhibition of protein synthesis, including the synthesis of microtubule protein .…”
Section: Discussionmentioning
confidence: 98%
“…Amato et al (1) reported similar responses in corn and cotton. Mann et al (19) found th,at trifluralin (11,12,17 If the vailtues for the sRNA l)eaks (I and I1) are combined and also those of the rRNA (IV, V, VI), )there ,is an increase in the sRNA fractions and a decrea,se in the 'rRNA fraction from 48 to 96 houirs in the control and treated roots. DNA (peak III) shows no change beltween treated and control roots from 48 to 96 hours, wh,ile tthe control shoots have a decreased amounit ait 96 hours and the treated shoots an increased amoSunit.…”
mentioning
confidence: 99%
“…1 This research was supported by funds from the Massachusetts Agricultural Experiment Station. The literature suggests that many herbicides act upon protein synthesis (7,27,31) and cell membrane permeability (6,26). Dicamba was reported to inhibit leucine incorporation into protein in soybean hypocotyl sections and to inhibit induction of a-amylase in barley aleurone layers (31).…”
mentioning
confidence: 99%